ECCLESIASTICAL ARCHITECTURE IN NIGERIA: EXPLORING UNIFYING ELEMENTS IN THE DESIGN OF WORSHIP CENTERS - Jamila, Bala Anita Alaere; Brisibe, Warebi Gabriel (International Journal of Research -GRANTHAALAYAH, 2022)
The primary factor in ecumenism has been the church’s unity. The World Council’s Central Committee produced an agreed-upon definition of ecumenical in 1951. The word derives from the Greek word for inhabited earth, and it refers to the church and its efforts to spread the Gospel over the world. As a result, ecumenism is linked to the Christian faith’s unique unity and mission in the context of the entire globe. In Nigeria, some State Governments have attempted to unify the key denominations of the Christian faith in an attempt to pursue this common mission by literarily bringing them under one roof. In other to achieve that, markers, and features of scared spaces for each of these denominations have to be identified and combined where possible. This paper explores how elements have been unified in the design of these Government initiated archetype.